Immune Cells Profiles in the Different Sites of COVID-19-Affected Lung Lobes in a Single Patient - Iwabuchi, Sadahiro; Miyamoto, Kyohei; Hatai, Mayuko; Mikasa, Yurina; Katsuda, Masahiro; Murata, Shin-ichi; Kondo, Toshikazu; Yamaue, Hiroki; Hashimoto, Shinichi (Frontiers in Medicine, 2022)
Whereas the COVID-19 disease pathophysiology is under investigation, it is important to identify the pathways of viral transmission and inflammation from the pre-illness to the disease-onset stages. We analyzed five lung lobes from a patient with COVID-19 who finally died after prolonged lung protective ventilation. Pathological examination revealed moderate inflammation in upper lung lobes and uneven yet severe inflammation and diffuse alveolar damage in lower lung lobes. SARS-CoV-2 was detected at higher levels not in severely, but rather moderately inflamed middle lung lobes, and immunohistochemistry and bulk RNA-sequencing results showed that immune cells were detected at higher levels in lower lung lobes. The mRNA expression of cytokine families varied. We found an increase in keratin 5- or aquaporin 3- expressing basal cells in the severely inflamed lower lung lobes, and the alveolar stromal tissues were filled with them. Thus, this analysis of lung samples from a patient helps to determine the COVID-19 pathophysiology at a specific time point, and the virus localization and inflammatory responses at each site of the lungs provide various important indications.